Cretaceous/Tertiary Boundary from the Koraljka-1 Off-Shore Well (SW of Zadar, Adriatic Sea) - Dubravko Lučić; Josip Benić; Damir Stanković; Danica Miletić (Geologia Croatica, 2010)
Deep exploration well Koraljka-1 in the central part of the Adriatic Sea was drilled through Neogene and Paleogene deposits and penetrated the Upper Cretaceous. In the interval from 2500 to 2230 m, the Cretaceous and Paleogene deposits consist of white to grey, mud-supported, fairly fossiliferous deeper-water, chalky limestone (wackestone-mudstone) with sporadic occurrences of chert, intercalated with bioclastic limestone packstone/rudstone to floatstone. Bioclastic limestone (calcarenite) intercalations, which yield platform-derived detritus, were redeposited seaward on the deep platform slope by a gravity mechanism. Lithostratigraphically, sedimentation was almost continuous across the Cretaceous - Tertiary boundary. The importance of these deposits and their stratigraphic interest is based on the fact that there is no on-shore equivalent of such deeper-water deposits in the Croatian part of the Outer Dinarids. In biostratigraphic terms, the K/T boundary is marked by significant changes in the microfossil assemblages (calcareous nannofossils, plankton and benthic foraminifera), which revealed that the hiatus at the boundary is minimal.